1997
DOI: 10.2307/3867542
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Policy and Long-Run Growth

Abstract: This paper discusses in a systematic and comprehensive way the existing literature on the relationship between the growth of countries' economies and various public finance instruments, such as tax policy, expenditure policy, and overall budgetary policy, from the perspectives of allocative efficiency, macroeconomic stability, and income distribution. It reviews both the conceptual linkages between each of the instruments and growth and the empirical evidence on such relationships. It broadly concludes that fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
102
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(113 citation statements)
references
References 79 publications
7
102
0
4
Order By: Relevance
“…We put forward a contradictory argument for Congo, that is, a positive result in conformity to Devarajan, Swaroop and Zoo (1996) results. These authors approve Easterly and Rebelo (1993) and later Tanzi and Zee (1997) results which advocate for a differentiation between direct and indirect effects of public expenditures upon economic growth. In principle, current public expenditures support demand and cause a short term GDP increase through Keynesian multiplier effect.…”
Section: Results Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We put forward a contradictory argument for Congo, that is, a positive result in conformity to Devarajan, Swaroop and Zoo (1996) results. These authors approve Easterly and Rebelo (1993) and later Tanzi and Zee (1997) results which advocate for a differentiation between direct and indirect effects of public expenditures upon economic growth. In principle, current public expenditures support demand and cause a short term GDP increase through Keynesian multiplier effect.…”
Section: Results Discussionmentioning
confidence: 99%
“…4(1), March 2016 If during a short term period public expenditures affect economic growth through a public expenditure multiplier and that of transfers, they can in long run affect economic growth by two channels at least (Tanzi and Zee, 1997) in increasing directly economy capital stock through public investment in infrastructure or public enterprise investment, in increasing indirectly marginal productivity of production factors provided by private sector through education, health, and other services expenditures which contribute to the accumulation of human capital.…”
mentioning
confidence: 99%
“…With this distinction they argued that both sides of the government budget should be considered in estimating the impact of fiscal policy on growth, as their financing offset the growth-enhancing effects of productive expenditure. Gerson (1998) and Tanzi and Zee (1997) surveyed the theoretical and empirical literature on the effect of fiscal policy variables (tax policy, public expenditure policy, budget policy) on economic growth. They concluded that fiscal policy variables influenced economic growth through their impact on the determinants of growth.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…They found that the level of education expenditure and the growth rate of public infrastructure investment both exhibited a positive impact on the growth rate of the economy. Tanzi and Zee (1997) examined systematically the various ways that the main fiscal instruments (tax policy, public expenditure policy, budget policy) influenced economic growth through their impact on the determinants of growth. Yasin (2003) studied the relationship between government expenditure and economic growth.…”
Section: Review Of Related Literaturementioning
confidence: 99%